Transfer or not to transfer? a medical dilemma - Singh, Neeta; Patel, Garima; Saini, Monika; Sethi, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Morphological assessment predominantly determines the quality of embryos although, several methods are available for it. Dilemma to transfer arises when clinicians are left with mere poor grade embryos. This case report encompasses a case of 37 years primary infertile female managed with GnRH antagonist cycle for tubal factor infertility. Post ovarian stimulation and ovum pickup, only two 4 celled grade-C embryos were available for transfer. Reluctantly the embryo was transferred, but fortunately resulted in a healthy live intrauterine pregnancy. This case report questions the aptness of the current methods to determine embryo quality and also enlightens whether the ethical or medical conundrum holds true regarding relation between embryo quality and chances of a fruitful pregnancy.